The Characteristics of the Delta Variant of SARS-CoV-2 Virus – the Dominant Agent of the Third and Forth Waves of Epidemic COVID-19 in Russia - T. E. Sizikova; V. N. Lebedev; D. A. Kutaev; S. V. Borisevich (Вестник войск РХБ защиты)
Among the epidemic variants of the SARS-CoV-2 virus the main attention is currently attracted by the delta variant (B.1.617), first identified in India in the end of 2020. Since the appearance of the delta variant, the morbidity rate of COVID-19 in India has increased 20-fold. The overflow of the delta variant of the SARS-CoV-2 virus outside of India is one of the factors in the emergence of the third wave of the COVID-19 pandemic. As of August 24, 2021 the delta variant of SARS-CoV-2 virus has been identified in 193 countries. The purpose of this work is to analyze the delta variant of SARSCoV-2 virus and the features of the disease caused by it. The main features of the delta variant are: a set of mutations affecting a significant functional area of S-protein; a transfer rate from person to person; a reduced incubation period of caused disease. In Russia, the delta variant of SARS-CoV-2 virus appears no earlier than the end of April – beginning of May, 2021. The spread of the delta variant as the dominant one is associated with the emergence in early June 2021 of the third, and in mid-September – the fourth wave of the COVID-19 epidemic in Russia. The epidemiological data for Russia show a sharp increase in the number of new cases of the disease, with a simultaneous increase in the number of hospitalizations and deaths of the disease. The necessary measures to combat the epidemic are: first of all, accelerating the pace of vaccination, as well as the set of administrative measures, including limiting mass events, strict observance of the mask regime and social distance in public places.